A Pattern of Inter-Religious Reconciliation by Buddhist Peaceful Means: An Analytical Case Study of Anti-Buddhist Violence in Ramu 2012, Cox’s Bazar, Bangladesh - Barua, Lablu (Journal of International Buddhist Studies, 2023)
This research consists of three main objectives: 1) To analyze the contexts, causes, and impacts of the anti-Buddhist violence in Ramu 2012, Cox’s Bazar, Bangladesh, 2) To synthesize the Buddhist Peaceful Means for inter-religious reconciliation between Buddhist and Muslim communities in Ramu, Cox’s Bazar, Bangladesh, 3) To present the pattern of the inter-religious reconciliation by Buddhist peaceful means in anti-Buddhist violence area in Ramu, Cox’s Bazar, Bangladesh. The methodology of this research applied a qualitative approach comprising documentary-based and in-depth interviews method. The research has been conducted over the 18th month through primary and secondary data collection and fourteen in-depth interviews with the main actors from this field and synthesized data to present the interreligious reconciliation pattern in Ramu, Cox’s Bazar, Bangladesh. Buddhism was one of the early religions in Bengal of Bangladesh, and the cause of anti-Buddhist violence were interest-based conflicts and cultural identity-based violence related to internal and external factors. The impacts of violence were social and communal harmony destroyed, misunderstanding and anger, and trust and social cohesion distanced and de-escalated Buddhist-Muslim relations in Ramu, Cox’s Bangladesh. Further, this research explained the concept of peace and inter-religious reconciliation from a Buddhistic point of view. It deliberated on the relevant teachings of Buddha for conflict resolutions and the inter-religious reconciliation pattern. The sum of the accumulated idea of this research is that reconciliation is a symbol and a path to peace and friendship in the communities and build trust and live as relatives in a good neighborhood through reconciliation, conflict resolution processes, social engagement activities, and practical actions. Buddhist Peaceful means four sublime minds, Eight Noble paths, Karma, interfaith dialogue, Negotiations, compromise, inquiry and forgiveness, and tolerance applied for the inter-religious reconciliation pattern in the Buddhist and Muslim communities in Ramu, Cox’s Bazar, Bangladesh.